TODAY'S CHILD -TOMORROW'S CREATOR (Academicia Globe: Inderscience Research, 2022)
This article describes the history of the Lankan game and the fact that today a lot of practical work is being done in the world and in our country to develop, preserve and pass on intangible heritage - ethnosport, national and traditional games to future generations.